Radiofrequency-induced endometrial ablation for the treatment of postpartum hemorrhage after vaginal delivery: Case report. Issue 52 (December 2017) - Wangping, Zhang; Hanbing, Wu
Abstract: Rationale: Postpartum hemorrhage is a common complication and difficult problem in obstetrics. Radiofrequency-induced endometrial ablation (RFIEA) widely used in abnormal uterine bleeding and achieved good effects. This article will investigate the effect of RFIEA for treatment of postpartum hemorrhage. Patients concerns: A 26-year-old healthy full-term parturient woman presented with postpartum hemorrhage after vaginal delivery for 11 hours, who was ready to emergency surgery (hysterectomy) 7 hours after inserting an intrauterine balloon into uterine cavity. Diagnoses: Blood loss after vaginal delivery was more than 500 mL during 11 hours in the full-term parturient woman. Intervention: We applied RFIEA to treatment of postpartum hemorrhage. With the patient in dorsal lithotomy position, we advanced the disposable device according to the instruction and operated the Novasure system in semi-automatic mode. Outcomes: There was no obvious endometrial bleeding found with hysteroscopy at the end of surgery. No complications (such as thermal injury to adjacent tissue, uterine perforation, bowel perforation) were observed. Lessons: It is safe and effective to treat postpartum hemorrhage after vaginal delivery using RFIEA.